2017
DOI: 10.1016/j.jad.2017.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Partially distinct combinations of psychological, metabolic and inflammatory risk factors are prospectively associated with the onset of the subtypes of Major Depressive Disorder in midlife

Abstract: Our data suggest that MDD subtypes are predicted by partially distinct combinations of baseline characteristics suggesting that these subtypes not only differ in their clinical manifestations but also in factors that contribute to their development. Subjects with minor depressive episodes, especially in combination with particular personality features, deserve close clinical attention to prevent the subsequent onset of atypical and melancholic major depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 83 publications
0
14
0
Order By: Relevance
“…However, considering that we found significant associations between MDD subtypes and cardiometabolic variables in our analyses, the absence of an effect of MDD subtypes on the associations between life-event stress and cardiometabolic variables is hardly attributable to the high prevalence of MDD. Hence, the absence of an effect of MDD subtypes on these associations is rather explained by the absence of an association between life-event stress and the atypical subtype (36), whereas this subtype has repetitively been shown to be associated with cardiovascular risk factors (33)(34)(35)(36). Conversely, the unspecified MDD subtype is likely to be strongly associated with life-event stress (36), but not with cardiovascular risk (34,35,49).…”
Section: Lifetime Psychosocial Stress and Cardiometabolic Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…However, considering that we found significant associations between MDD subtypes and cardiometabolic variables in our analyses, the absence of an effect of MDD subtypes on the associations between life-event stress and cardiometabolic variables is hardly attributable to the high prevalence of MDD. Hence, the absence of an effect of MDD subtypes on these associations is rather explained by the absence of an association between life-event stress and the atypical subtype (36), whereas this subtype has repetitively been shown to be associated with cardiovascular risk factors (33)(34)(35)(36). Conversely, the unspecified MDD subtype is likely to be strongly associated with life-event stress (36), but not with cardiovascular risk (34,35,49).…”
Section: Lifetime Psychosocial Stress and Cardiometabolic Riskmentioning
confidence: 99%
“…Studies have also revealed associations between psychosocial stress and major depressive disorder (MDD) (31) and between MDD and CVDs (32). Recent research suggests that the association between MDD and cardiometabolic risk factors is entirely attributable to the atypical depression subtype (characterized by increased appetite, increased sleep, and leaden paralysis) (33)(34)(35)(36). However, the interplay between psychosocial stress and psychological factors on the risk cardiometabolic abnormality has hardly been studied.…”
mentioning
confidence: 99%
“…However, investigations on neuroticism have been limited to a few inflammatory parameters: for example, C-reactive protein (CRP) or interleukin (IL)-6, for which the relationship with neuroticism could not be confirmed ( 6 ). Importantly, neuroticism is considered a risk factor for the development and onset of major depression and certain subtypes of depression ( 7 9 ). However, the biological mechanisms for this relationship are not yet well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have attempted to identify subtypes of depressive illness based on methodologies such as latent class analysis (Lamers et al, 2010) or causative factors (Rudaz et al, 2017). Different depression subtypes have been identified, comparable to MDD-MF and MDD-AF; the latter exhibiting a stronger association with obesity (Lamers et al, 2010;Levitan et al, 2012;Hasler et al, 2004;Glaus et al, 2013).…”
Section: Directionality Of Obesity-depression Associationsimportance mentioning
confidence: 99%